Thirteen-Year Trends in Child and Adolescent Fundamental Movement Skills - Louise L. Hardy; Lisa M. Barnett; Paola Espinel; Anthony D. Okely (2013)
The objective of this study is to describe 13-yr trends in children's fundamental movement skill (FMS) competency.Secondary analysis of representative, cross-sectional, Australian school-based surveys was conducted in 1997, 2004, and 2010 (n = 13,752 children age 9-15 yr). Five FMS (sprint run, vertical jump, catch, kick, and overarm throw) were assessed using process-oriented criteria at each survey and children's skills classified as competent or not competent. Covariates included sex, age, cardiorespiratory endurance (20-m shuttle run test), body mass index (kg·m), and socioeconomic status (residential postcode).At each survey, the children's FMS competency was low, with prevalence rarely above 50%. Between 1997 and 2004, there were significant increases in all students' competency in the sprint run, vertical jump, and catch. For boys, competency increased in the kick (primary) and the overarm throw (high school), but among high school girls, overarm throw competency decreased. Between 2004 and 2010, competency increased in the catch (all students), and in all girls, competency increased in the kick, whereas competency in the vertical jump decreased.Overall, students' FMS competency was low especially in the kick and overarm throw in girls. The observed increase in FMS competency in 2004 was attributed to changes in practice and policy to support the teaching of FMS in schools. In 2010, competency remained low, with improvements in only the catch (all) and kick (girls) and declines in vertical jump. Potentially, the current delivery of FMS programs requires stronger positioning within the school curriculum. Strategies to improve children's physical activity should consider ensuring children are taught FMS to competency level, to enjoy being physically active.